Compromised Blood–Brain Barrier Integrity Is Associated With Total Magnetic Resonance Imaging Burden of Cerebral Small Vessel Disease - Li, Yue; Li, Man; Zuo, Long; Shi, Qinglei; Qin, Wei; Yang, Lei; Jiang, Tao; Hu, Wenli (Frontiers in Neurology, 2018)
Objective: Several studies have demonstrated that compromised blood–brain barrier (BBB) integrity may play a pivotal role in the pathophysiology of individual cerebral small vessel disease (cSVD) markers, but the association of BBB permeability with to-tal magnetic resonance imaging (MRI) cSVD burden remains unclear. This study aimed to investigate the relationship between BBB permeability and total MRI cSVD burden. Methods: Consecutive participants without symptomatic stroke history presented for physical examination were enrolled in this cross-sectional study. The presence of lacunes, white matter hyperintensities (WMH), cerebral microbleeds, enlarged peri-vascular spaces were recorded in an ordinal score (range 0-4). We used dynamic con-trast-enhanced (DCE)-MRI and Patlak pharmacokinetic model to quantify BBB per-meability in the normal-appearing white matter (NAWM), WMH, cortical gray matter (CGM) and deep gray matter (DGM). Results: All 99 participants averaged 70.33 years old (49-90 years). Multivariable line-ar regression analyses adjusted for age, sex and vascular risk factors showed that leak-age rate and area under the leakage curve in the NAWM, WMH, CGM and DGM were positively associated with total MRI cSVD burden (all P < 0.01). Moreover, fractional blood plasma volumes in the NAWM, CGM and DGM were negatively associated with total MRI cSVD burden (all P < 0.05). Conclusions: This study verified that compromised BBB integrity is associated with total MRI cSVD burden, suggesting that BBB dysfunction may be a critical contributor to cSVD pathogenesis. Longitudinal studies are required to determine whether there is a causal relationship between BBB permeability and total MRI cSVD burden.